2008
DOI: 10.1016/j.cherd.2008.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Standard deviation of absolute and differential pressure fluctuations in fluidized beds of group B particles

Abstract: Keywords: Fluidization; Gas-solid bed; Pressure fluctuations IntroductionKnowledge of bed fluctuations in a gas-solid fluidized bed is important for its design and/or operation as they provide information on indexes of fluidization quality, which include formation, rise and eruption of gas bubbles, movement of solids and pressure waves propagation through the bed. These indexes are commonly considered as an indicative of the dynamic behaviour of the fluidized bed and can be explored as a way of monitoring the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…The variations in the two deviations were often used to determine the regime transformation (Salehi-Nik et al, 2009;van Ommen et al, 2004;Sobrino et al, 2008), while it was unsuccessful for the DCC in present work. As a result, higherorder moments, skewness (third moment) and kurtosis (fourth moment) were given for insight into DCC.…”
Section: Discussionmentioning
confidence: 99%
“…The variations in the two deviations were often used to determine the regime transformation (Salehi-Nik et al, 2009;van Ommen et al, 2004;Sobrino et al, 2008), while it was unsuccessful for the DCC in present work. As a result, higherorder moments, skewness (third moment) and kurtosis (fourth moment) were given for insight into DCC.…”
Section: Discussionmentioning
confidence: 99%
“…Standard deviation of signals from fluidized beds have been used to identify regime transitions (Bi et al, 2000;Azizpour et al, 2011), determine the minimum fluidization velocity (Sobrino et al, 2008;Abbasi et al, 2009) and detect defluidization in industrial fluidized-bed reactors as an on-line tool . Standard deviation of time series x i shows the deviation of the distribution from a normal distribution in time interval of N and is defined as follows:…”
Section: Time Domain Analysismentioning
confidence: 99%
“…Standard deviations of the pressure fluctuations has been widely used to identify a regime change in gas-solid fluidized beds [26][27][28][29][30]. Table 2 shows the averaged values and standard deviations of differential pressure fluctuations collected at different bed sections in a spouted bed.…”
Section: Figurementioning
confidence: 99%
“…In the literature, it has been reported that A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 4 the standard deviation or the average absolute deviation is often used to identify a flow regime change [26][27][28][29][30]. The statistical analysis in time domain is the simplest and the most commonly employed; it is also very fast and easily applicable.…”
Section: Introductionmentioning
confidence: 99%